Newly Developed Graft Failure Detected Using Computed Tomography Within 1 Year After Coronary Artery Bypass Grafting Surgery: One Single-Center Experience - Li, Zhaoshui; Qiao, Youjin; Sheng, Wei; Chi, Yifan (Frontiers in Cardiovascular Medicine, 2022)
BACKGROUND Newly developed graft failure negatively affects the short- and long-term outcomes of patients who experience CABG surgery. This study explored the value of transit TTFM parameters for predicting the risk of newly developed graft failure that occurrs within one year after CABG, as well as investigated the relationship between newly developed graft failure and adverse cardiovascular events METHODS A total of 134 patients who underwent CABG and had CTA data (1 year postoperatively) were divided into two groups: the patient group, in which patients did not have newly developed graft failure, and the occluded group, in which patients developed newly developed graft failure between 1 and 12 months after CABG. The patency rate of grafts in different targets was analyzed. The correlations between graft failure and TTFM parameters and between graft failure and the occurrence of adverse cardiovascular events were investigated. RESULTS The overall rate of newly developed graft failure was 7.2%, the venous graft failure was 10.8%, and the arterial graft failure was 0.7%. The occluded group had a higher pulse index (PI) (2.9 vs 2.4, P = 0.007), a lower graft flow volume (MGF) (20.0 ml/min vs 25.0 ml/min, P = 0.028), and a lower diastolic flow fraction (DF) (63.5% vs 70.0%, P = 0.019) than the patent group. The cut-off value for predicting newly developed graft failure was PI > 2.75 (P = 0.007), MGF < 23.5 ml/min (P = 0.030), and DF < 65.5% (P = 0.019). Compared with the patent group, the newly developed graft failure group had higher rates of recurrent angina (13.6% vs 0.9%, P = 0.0014) and revascularization intervention (9.1% vs 0.0% P = 0.026). However, there were no differences in death, cardiac death, myocardial infarction, and cerebral infarction after CABG operation between these two groups (P > 0.05). CONCLUSIONS High PI and low MGF and DF are risk factors for newly developed graft failure. The patients with newly developed graft failure had higher rates of recurrent angina and revascularization intervention. TTFM parameters may be used to predict the occurrence of newly developed graft failure in patients after CABG surgery.